The current state of sustainability reporting: opportunities and challenges for consultancy companies. Overcoming marketing challenges through business models - Moreira, Beatriz (2023)
Non-Financial reporting is undoubtedly becoming an increasingly prevalent practice in modern society in order to ensure transparency concerning an organization's contributions to sustainable development. The case study covers the first steps of The Company implementing a non-financial reporting software that aims to integrate “sustainability” into the enterprise’s business strategy to keep up with increasingly demanding sustainability regulations and the challenges they faced during that process. Afterward, in the individual teaching note, these challenges are explored solution wise. Finally, in the project evaluation report, it is discussed the opportunity of implementing that software in the Portuguese market and it is provided recommendations in order for them to thrive.